Brain Tumor Segmentation using Multiobjective Fuzzy Clustering - Limam, Olfa Mohamed (Transactions on Engineering and Computing Sciences, 2016)
The segmentation of magnetic resonance images plays a crucial role in medical image analysis because it extracts the required area from the image. Despite intensive research, it still remains a challenging problem and there is a need to develop an appropriate and efficient medical image segmentation method. In this paper, we propose a clustering approach for brain tumor segmentation to diagnose accurately the region of cancer. Applied to magnetic resonance image brain our method provides better identification of brain tumor.